2013
DOI: 10.1007/s10551-013-1997-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership and Reputation: Combined Indirect Effects on Organizational Deviance

Abstract: The interest in ethical leadership has grown in the past few years, with an emphasis on the mechanisms through which it affects organizational life. However, research on the boundary conditions that limit and/or enhance its effectiveness is still scarce. Thus, the present study examines the relationship between ethical leadership and affective commitment to the organization, as a reflection of the quality of the employee-organization relationship (EOR) and proposes this relationship is conditional on the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 61 publications
5
65
0
4
Order By: Relevance
“…The findings revealed that ethical leadership affects all employee work attitudes (i.e., AC‐ORG, AC‐SUP, and job satisfaction) being studied. The results were consistent with those of previous research demonstrating that ethical leadership is positively linked to AC‐ORG (Demirtas & Akdogan, ; Hansen et al, ; Kim & Brymer, ; Neubert et al, , ; Neves & Story, ; Pucic, ), AC‐SUP (Hansen et al, ), and job satisfaction (Neubert et al, ; Okan & Akyüz, ; Yang, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings revealed that ethical leadership affects all employee work attitudes (i.e., AC‐ORG, AC‐SUP, and job satisfaction) being studied. The results were consistent with those of previous research demonstrating that ethical leadership is positively linked to AC‐ORG (Demirtas & Akdogan, ; Hansen et al, ; Kim & Brymer, ; Neubert et al, , ; Neves & Story, ; Pucic, ), AC‐SUP (Hansen et al, ), and job satisfaction (Neubert et al, ; Okan & Akyüz, ; Yang, ).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the current research have implications for future research. First, the effects of ethical leadership on employee work attitudes in the business context in Thailand seem to be the same as in other countries (Demirtas & Akdogan, ; Hansen et al, ; Kim & Brymer, ; Neubert et al, , ; Neves & Story, ; Okan & Akyüz, ; Pucic, ; Yang, ). However, the transactional element might be different in different cultures or contexts (Brown & Treviño, ).…”
Section: Discussionmentioning
confidence: 79%
“…That is, ethical leadership had both direct and indirect (over teachers' work attitudes) effects on school effectiveness meaning that ethical leadership behaviours contribute to school effectiveness and that this could at least partly be explained by an improved affective commitment and job satisfaction of the teachers. Parallel to this result, many field studies indicated that administrators' ethical leadership behaviours are associated with employees' work attitudes (Avey et al, 2012;Çelik et al, 2015;Frisch and Huppenbauer, 2014;Hassan et al, 2014;Kim and Brymer, 2011;Loi et al, 2015;Madenoğlu et al, 2014;Neves and Story, 2015;Ogunfowora, 2014). Brown et al (2005) and Brown and Treviño (2006) stated that ethical leadership's effect on employee attitudes and behaviours can be explained by social exchange theory.…”
Section: Discussionmentioning
confidence: 91%
“…Although Meyer and Allen (1991) have suggested a three-dimensional construct of organizational commitment (e.g., continuous, normative, and affective), many studies on the link between ethical leadership and employee commitment (Hassan et al, 2014;Loi et al, 2015;Neves and Story, 2015;Ng and Feldman, 2015) have studied organizational commitment on the basis of affective commitment, which is characterized by emotional attachment, organizational identification and involvement. Therefore, the current study, the affective commitment dimension was used to examine organizational commitment.…”
Section: Ethical Leadership and Work Attitudesmentioning
confidence: 99%
“…Avey et al, 2011;Neves & Story, 2015), comportamentos contraprodutivos (e.g. Den Hartog & Belschak, 2012;Demirtas, 2013;Mayer, Kuenzy, & Greenbaum, 2011), rotatividade (e.g.…”
Section: Efeitos Da Liderança éTicaunclassified